2013
DOI: 10.1590/s2238-10312013000200019
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment in airlines stocks market

Abstract: In this paper we compared the results between stock portfolios of North American and European airlines. The model accesses the market risk using Value-at-Risk approach in both portfolios over one month period. The analysis was performed through the use of GARCH-EVT methods and Student’s-t Copula with a Monte Carlo Simulation. The assets in the financial market usually present heavy tails in their probability distributions, so, a process capable to deal with this issue is crucial to measure the risk of loss. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Comparing the performance of North American and European airlines' stock portfolios, Sato (2013) finds that the global financial crisis of 2008-09 has a major effect on the North American market compared to the European one. The fluctuation in aviation market is the result of both internal and external factors, and the development of financial instruments plays an important role on the liquidity dependence of investment.…”
Section: Impacts Of the Pandemic On The Transportation Industrymentioning
confidence: 99%
“…Comparing the performance of North American and European airlines' stock portfolios, Sato (2013) finds that the global financial crisis of 2008-09 has a major effect on the North American market compared to the European one. The fluctuation in aviation market is the result of both internal and external factors, and the development of financial instruments plays an important role on the liquidity dependence of investment.…”
Section: Impacts Of the Pandemic On The Transportation Industrymentioning
confidence: 99%
“…Comparing the performance of North American and European airlines' stock portfolios, Sato (2013) finds that the global financial crisis of 2008–2009 has a major effect on the North American market compared to the European one. The fluctuation in aviation market is the result of both internal and external factors, and the development of financial instruments plays an important role on the liquidity dependence of investment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Borenstein and Zimmerman (1988) [2] use CAPM market model to analyze the impact of 74 plane crashes on the airline sector in the US from the 1960s to 1985.They reported that airline crashes has an adverse impact on the revenue growth. Sato (2013) [17] Comparing the performance of European airline and North American stock portfolios, points out the 2008 global financial crisis has a main effect on the North American market compared to the European one. Sakkakom and Suntichai (2020) examined the shortrange impact of the new COVID-19 pandemic on 52 listed aviation companies across the globe by using event study methodology.…”
Section: International Events and Aviation Industrymentioning
confidence: 99%